Innovating the Filipino pandesal: a consumer preference study - Ricafrente, Camille P. Aninipot, Marvin Trinos, Jefferson Czar Y. Ibanez, Patricia Mari G. 4 0 16; 5 (2016)
NO ABSTRACT.
Undergraduate Thesis: (B.S. in Hotel snd Hospitality Management) Pamantasan ng Lungsod ng Maynila 2016.
Keywords: 2 -- 0; 6; 20; 20; 2